GAMBARAN SELF-ESTEEM SISWA KORBAN CYBER BULLYING - Puri Indriani Indah; Heris Hendriana; Rima Irmayanti (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2021)
This research is motivated by the current pandemic condition which affects the implementation of guidance and counseling services, especially career guidance services for students of SMK Nuurul Muttaqiin, where currently students experience confusion in career choices and decisions. This is aimed at the results of observations to students of SMK Nuurul Muttaqiin class XII, during this pandemic they have difficulty in determining the appropriate choice of work and choice of university majors because they do not get optimal and direct guidance from counselors or counselors. The form of efforts made in counseling guidance services to provide students with understanding of career maturity, namely through career guidance services. This research was conducted with a qualitative research approach. The data collected in this study are data obtained by means of interviews, observation and documentation study. The subjects in this study were five students who had difficulties in determining careers after graduating from vocational school and BK coordinators. The form of career counseling services at SMK Nuurul Muttaqiin begins with several stages, namely classical guidance, group guidance, and individual counseling.Keywords: career guidance, career maturity.